Proceedings of the Twenty-Seventh International Joint Conference on Artificial Intelligence 2018
DOI: 10.24963/ijcai.2018/461
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Complex Activities from Ongoing Multivariate Time Series

Abstract: The rapid development of sensor networks enables recognition of complex activities (CAs) using multivariate time series. However, CAs are usually performed over long periods of time, which causes slow recognition by models based on fully observed data. Therefore, predicting CAs at early stages becomes an important problem. In this paper, we propose Simultaneous Complex Activities Recognition and Action Sequence Discovering (SimRAD), an algorithm which predicts a CA over time by mining a sequence of multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
(7 reference statements)
0
16
0
Order By: Relevance
“…In this way, the mutual profound extractor uses the priori of basic tasks which are components of a composite operation. In comparison to joint research, [125] uses two conditional probabilistic models to infers a series of basic events and their resulting composite operation. The authors used an approximate sequence of acts to infer the composite behavior where time differences between single activities are drawn for the classification of the composite behavior.…”
Section: E Complex Activitiesmentioning
confidence: 99%
“…In this way, the mutual profound extractor uses the priori of basic tasks which are components of a composite operation. In comparison to joint research, [125] uses two conditional probabilistic models to infers a series of basic events and their resulting composite operation. The authors used an approximate sequence of acts to infer the composite behavior where time differences between single activities are drawn for the classification of the composite behavior.…”
Section: E Complex Activitiesmentioning
confidence: 99%
“…Literature indicates large number of early classification approaches for time series data. These approaches addressed the problems from wide range of research areas including healthcare [46]- [48], [61]- [63], human activity recognition [8], [43], [44], industry [34], [51], [64], and so on. After making comprehensive survey, we found that UTS has attracted more researchers than MTS.…”
Section: B Categorization Of Early Classification Approachesmentioning
confidence: 99%
“…3) Model based early classification: Another set of early classification approaches [34], [42], [44], [49], [55], [58], [69] proposed mathematical models based on conditional probabilities. The approaches obtain these conditional probabilities by either fitting a discriminative classifier or using generative classifiers on training.…”
Section: ) Prefix Based Early Classificationmentioning
confidence: 99%
See 2 more Smart Citations